Senegal: A service economy in need of an export boost - E. Philip English (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper first summarizes the macroeconomic and trade performance of Senegal, emphasizing the limits of traditional exports. It then focuses on three export sectors which have had some success in the past and have good potential for future growth: tourism, horticulture and information technology-enabled services. Sector-specific constraints are identified including beach erosion and hotel quality (tourism), access to land (horticulture), and lack of competition and skilled labour (information technology). Common problems include the absence of strategies and reliable data, tax administration, and the need for a stronger dialogue with the private sector.
Keywords: 330; exports; services; tourism; horticulture; telecommunications